Analytical solution of the non-discretized radiative transfer equation for a slab of finite optical depth - Efimov, Garij V.; Waldenfels, Wilhelm von; Wehrse, Rainer (Journal of quantitative spectroscopy & radiative transfer, 1995)
An analytical solution of the radiative transfer equation for a plane parallel slab of finite depth is presented without requiring discretization in space or angles. The solution, expressed in terms of the matrix hyperbolic tangent function, avoids the problem of exponentially increasing terms so that it is also suitable for numerical calculations. By using the resolvent of the transfer equation we obtain simple series expansions for the matrix elements.
Elektronische Reproduktion der Druck-Ausgabe 5. April 2000
Gesehen am 23.05.2023